2014
DOI: 10.7150/ijms.8407
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Spectrum of the NKX2-5 Gene in Patients with Lone Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common form of sustained cardiac arrhythmia in humans and is responsible for substantial morbidity and mortality worldwide. Emerging evidence indicates that abnormal cardiovascular development is involved in the pathogenesis of AF. In this study, the coding exons and splice sites of the NKX2-5 gene, which encodes a homeodomain-containing transcription factor essential for cardiovascular genesis, were sequenced in 146 unrelated patients with lone AF as well as the available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 69 publications
1
29
0
1
Order By: Relevance
“…** P<0.01 and * P<0.005, compared with the same quantity of wild-type NKX2.5. ANF, atrial natriuretic factor; NKX2.5, NK2 homeobox 5. homeodomain 2 (11,19,26,29,31,48,49). The NKX2.5 mutation of p.Q181X identified in the present study was located in the HD, and functional analyses revealed that the mutant protein showed loss of the ability to transcriptionally activate ANF, alone or together with GATA4.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…** P<0.01 and * P<0.005, compared with the same quantity of wild-type NKX2.5. ANF, atrial natriuretic factor; NKX2.5, NK2 homeobox 5. homeodomain 2 (11,19,26,29,31,48,49). The NKX2.5 mutation of p.Q181X identified in the present study was located in the HD, and functional analyses revealed that the mutant protein showed loss of the ability to transcriptionally activate ANF, alone or together with GATA4.…”
Section: Discussionmentioning
confidence: 48%
“…In humans, the NKX2.5 gene is mapped to chromosome 5q34, coding for a protein of 324 amino acids, which is expressed at a high level in the human heart (11). The NKX2.5 protein contains an evolutionarily conserved homeodomain (HD), which is centrally located at amino acid positions 138-197, and functions to specifically recognize and bind to a consensus DNA motif, AAGTG, which is key in the transcriptional regulation of target genes, including ANF, brain natriuretic peptide and α-actin, either alone or in synergy with other transcription factors, including GATA4, TBX5, TBX20, heart and neural crest derivatives expressed 2 and paired-like .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Implicated genes include those encoding connexin 40, GJA5 [7, 6769], the transcription factor gene NKX2.5 [70, 71], and the LMNA gene[72]. Genes involved in the renin-angiotensin-aldosterone pathway, including the angiotensin converting enzyme, angiotensin gene promoter and angiotensinogen[7376], have also been associated with AF.…”
Section: Polygenic Non-familial Common Afmentioning
confidence: 99%